Dry matter accumulation in two sunflower cultivars at three planting dates - Sangoi, Luis; Silva, Paulo Regis Ferreira da (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out in order to study dry matter accumulation in the different plant parts of two sunflower cultivars, Contisol 711 and Contisol, during grain filling stage at three planting dates, September 5, October 14 and December 14. It was conducted in Guaíba, Rio Grande do Sul State, Brasil, during 1983/84 growing season. Samples were collected weekly from the emergence of first anther until all leaves were senescent. Plants were separated in green leaves, senescent leaves, stems, heads and grains. Linear and quadratic regressions, logarithmic and exponential functions were adjusted to the data obtained. Biological yield, heads and grain weight were higher at September planting date, regardless of cultivar. At this date, for both cultivars all organs had a longer duration. Contisol showed higher biological yieid, leaf and stem weight than 'Contisol 711', in all planting dates.